Psychosocial Services for Students in Metro Manila Universities Offering Social Work Degree Programs - Cauilan, Maria Alexandria; Reyes, Jose Ramil (Asean Social Work Journal, 2022)
The state of mental health among Filipino college students remains a major concern, especially in the context of the pandemic. Cases of mental health-related problems have been seen to have risen, particularly among tertiary-level students. Fortunately, academic institutions are working to address these ongoing issues that hinder students' social functioning. However, there is a need for further research on the actual presence of psychosocial support services in universities to know and understand how school systems address the concerning problem about the mental health of their students. Identifying and discerning these support systems, as well as the gaps that come with them, is crucial in providing relevant knowledge and information for the students, faculty, and university administrators alike, to be more aware of the pressing need to come up with strategies and plans in the form of equipping more effective and more efficient psychosocial support systems to ultimately help college students in need. This paper identifies the psychosocial support systems in place among Metro Manila universities that offer social work degree programs, including the benefits, opportunities, risks, and challenges they have come across, to provide a background of what is happening and what is needed to attain social functioning, all for the students’ well-being.